Description of the termite genus Prohamitermes (Termitinae) with new characters from the Leuser Ecosystem, Sumatra, Indonesia - SAMSUL MUARRIF; SAMADI SAMADI; JAUHARLINA JAUHARLINA; SYAUKANI SYAUKANI (Society for Indonesian Biodiversity, 2023)
Abstract. Muarrif S, Samadi S, Jauharlina J, Syaukani S. 2023. Description of the termite genus Prohamitermes (Termitinae) with new characters from the Leuser Ecosystem, Sumatra, Indonesia. Biodiversitas 24: 6119-6125. Prohamitermes is a termite genus that belongs to the subfamily Termitinae, alongside 61 other genera, within the family Termitidae. Termitidae, comprising 70% of all termite species, is the most prominent family in Isoptera. However, limited information about this Prohamitermes genus is available. Consequently, researchers and experts in the field have encountered challenges in acquiring comprehensive knowledge about the genus due to the need for more relevant literature. This paucity of information needs to improve our understanding of its characteristics, behavior, and ecological significance. Therefore, describing Prohamitermes is necessary to taxonomically identify termites from the subfamily Termitinae. This comprehensive study was meticulously conducted within the pristine Leuser Ecosystem (LE), employing a rigorously standardized transect protocol specifically developed to ensure accurate termite analysis. The genus is characterized by certain features present in its head capsule. Firstly, the shape of the front in a lateral view is a distinguishing characteristic, followed by the shape of the lateral sides (left and right) of the head capsule as observed from a dorsal view. While previous journals have described this termite genus based on the shape of its labrum and mandibles, this article focuses on the shape of its head capsule, specifically the front and lateral head capsule. Additionally, the article discusses the ecology of Prohamitermes. The morphological description presented in this study is expected to contribute to termite research, particularly in termite taxonomy and control.